The psychology of attitudes and attitude change - Forgas, Joseph P.; Cooper, Joel; Crano, William D., 1942- (Sydney Symposium of Social Psychology series ;, 2010)
Attitudes are central to understanding human beings' unique ability to create elaborate predispositions and evaluations based on their social experiences. This volume reviews cutting-edge research on attitudes by leading scholars and is essential reading for social psychologists, and practitioners in clinical, counseling, organizational, marketing, forensic, and developmental psychology.